Saving Ruby King - West, Catherine Adel (Park Row Books, 2020)
When Ruby King's mother is found murdered in their home in Chicago's South Side, the police dismiss it as another act of violence in a black neighborhood. But for Ruby, it's a devastating loss that leaves her on her own with her violent father. While she receives many condolences, her best friend, Layla, is the only one who understands how this puts Ruby in jeopardy. Their closeness is tested when Layla's father, the pastor of their church, demands that Layla stay away. But what is the price for turning a blind eye? In a relentless quest to save Ruby, Layla uncovers the murky loyalties and dangerous secrets that have bound their families together for generations. Only by facing this legacy of trauma head-on will Ruby be able to break free.